Case report: Dermatosis neglecta mimicking pemphigus foliaceus in association with obsessive–compulsive disorder - Wattanawinitchai, Kantarat; Suchonwanit, Poonkiat (Frontiers in Medicine, 2023)
Dermatosis neglecta (DN) is a frequently underrecognized skin disorder that occurs due to unconscious or conscious neglect of self-cleaning, causing the accumulation of keratin, sweat, sebum, and impurities. It is characterized by asymptomatic yellowish-to-brownish, waxy, adherent papules or plaques with cornflake-like scales that mimic several dermatological conditions. DN awareness is crucial for avoiding unnecessary invasive diagnostic procedures. Its lesions can be removed with some difficulty by ordinary cleansing and efficiently cleared with ethyl or isopropyl alcohol. Individuals with underlying physical or mental disabilities or psychiatric conditions are highly associated with DN. Nevertheless, supportive evidence for the coexistence of DN and psychological conditions is sparse, and most individuals with mental problems usually deny having psychiatric issues. Here, we present a case of DN resembling pemphigus foliaceus on the face with obsessive-compulsive disorder in a 16-years old male. The definitive diagnosis of DN in this patient was confirmed via histopathological examination. The lesions completely disappeared after appropriate facial cleansing and psychiatric management. DN may reveal underlying psychiatric disorders in patients.